Associations between putative risk factors and poor colostrum yield in Holstein Friesian cattle. (December 2022) - Borelli, Elena; Jonsson, Nicholas N.; Denholm, Katharine S.
Abstract: When dairy cows produce little or no colostrum, calves are likely to suffer from failure of passive transfer (FPT). Volume of colostrum produced by the dam may be affected by: nutrition; environmental conditions; time from calving to milking; parity; dry period length; calving difficulty; calf weight; calf sex; calf viability; cow BCS / body weight; milk production in previous lactation and dam health. While risk factors for poor IgG concentration in colostrum have been extensively studied, there is little published literature on low colostrum yields and associated risk factors. The aim of this observational study was to identify risk factors for poor colostrum yield in dairy cows and to quantify the effect of variation in those variables that the farmer can directly control (length of dry period, and close-up transition period nutrition) using inverse probability modelling. 439 animals from a single Scottish dairy farm were used as a convenience sample. First milking colostrum yield was measured by farmers using a graduated bucket. For each animal, risk factor data and meteorological data from the nearest weather were obtained. Decreased colostrum yield was associated with increasing daily temperature range, while increasing UV index, lactation number and number of days dry increased colostrum yield. Marginal effect models revealed that for each additional day of dry period, colostrum yield increased. Higher UV indices the month before calving were positively associated with colostrum yield, particularly in primiparous cows, and higher temperatures in the months before calving were positively associated with colostrum yield in all cows. Highlights: If cows fail to produce enough colostrum their calves are more likely to have high incidences of morbidity and mortality. Several risk factors might be responsible for poor colostrum yield in dairy cows. Lactation category, UV index, dry period length and temperature range were associated with poor colostrum yield. Monthly UV and temperature parameters were more closely related to colostrum yield in primiparous than multiparous animals.